Effect of annealing on activation of native acceptors in narrow-gap p-HgCdTe crystals - Bogoboyashchiy, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Hall effect, resistivity and p-n-junction characteristics were investigated on high pure and perfect p-type Hg₁₋xCdxTe crystals (x ~ 0.2) versus temperature, doping, and a way of heat treatment. It was shown, that activation energy of extrinsic acceptors does not depend on conditions of the crystal heat treatment, while the first native acceptor level increases monotonically from 10 meV in the Hg-saturated crystal up to 15.4 meV in the Te-saturated one. The experimentally observed energy of the first level of the native acceptor in Te-saturated crystals (15.4 meV) is in a good agreement with the value 16 meV, obtained by calculation carried out in the framework of the effective mass approximation. The difference between the crystals, saturated by Hg or Te, has an essential effect for reverse dark current through a p-n-junction at T = 77 K. It should be taken into account when manufacturing the photodiodes.